Workshop Pemanfaatan Aplikasi Filmora sebagai Alternatif Pembuatan Media Pembelajaran pada Guru Pondok Pesantren Ar-Rayyan Kabupaten Pacitan - Yoga Prisma Yoga; Alim Citra Aria Bima; Inung Diah Kurniawati; M. Fatkhur Rahman (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2025)
The development of information technology is very important in the world of education. Education taught in Islamic boarding schools is no exception. A teacher at an Islamic boarding school also needs to master technology in the field of multimedia in providing learning videos. This is done in order to help teachers deliver material in a more interesting way to their students. Therefore, a workshop on using Filmora as an alternative for making learning videos is needed. The methods used in this service activity are survey activities, preparation stage, implementation stage, and evaluation stage. The results obtained from this workshop activity were an increase in the abilities of the teachers at the Ar-Rayyan Islamic boarding school. Previously only around 30% of teachers were able to make learning videos, after the workshop was held there are now 85% of teachers who can use technology to make learning videos. Apart from that, the results of the questionnaire analysis distributed to the participants also obtained an average score of 4.1 which is in the good category. The participants (teachers) at the Ar-Rayyan Islamic Boarding School were very enthusiastic in taking part in the workshop activities that had been carried out.